Were there Religious Associations in Antiquity? - Kloppenborg, John S. (Ephemerides theologicae Lovanienses, 2024)
Despite recent challenges to the category of 'religious' or 'cultic' associations, the categorization of private associations as 'occupational', 'cultic', 'neighbourhood', 'diasporic' and 'domestic' remain useful heuristic categories whose utility can be defended by examining the particular ways that sociality in associations was materialized, whether through cultic, convivial, or other means.